Investment banking, reputation, and the underpricing of initial public offerings - Beatty, Randolph P.; Ritter, Jay R. (Journal of Financial Economics, 1986)
This paper develops and tests two propositions. We demonstrate that there is a monotone relation between the (expected) underpricing of an initial public offering and the uncertainty of investors regarding its value. We also argue that the resulting underpricing equilibrium is enforced by investment bankers, who have reputation capital at stake. An investment banker who ‘cheats’ on this underpricing equilibrium will lose either potential investors (if it doesn't underprice enough) or issuers (if it underprices too much), and thus forfeit the value of its reputation capital. Empirical evidence supports our propositions.